2014
DOI: 10.4049/jimmunol.1303435
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Form of IL-27Rα Is a Natural IL-27 Antagonist

Abstract: IL-27 is a cytokine of the IL-12 family that plays a key role in the regulation of inflammatory and T cell responses. Its receptor is composed of IL-27Rα and gp130 and activates the STAT pathway. We show in this study, using an ELISA that we developed, that a naturally occurring soluble form of IL-27Rα (sIL-27Rα) is produced by human activated CD4+ and CD8+ T cells, B cells, myeloid cells, and various cell lines. sIL-27Rα is present at a mean concentration of 10,344 ± 1,274 pg/ml in the sera from healthy indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 43 publications
3
43
0
Order By: Relevance
“…In contrast to sgp130, the authors found no evidence for alternative splicing of the WSX-1 mRNA, but rather showed that metalloproteases were responsible for the generation of sWSX-1. They reported serum levels of about 10 ng/ml in healthy humans, and an increase in sWSX-1 levels in the serum of patients suffering from Morbus Crohn [97]. These data suggest that sWSX-1 acts a natural antagonist of IL-27 signaling in vivo, comparable to the role of sgp130 for IL-6 trans-signaling [18,94].…”
Section: A Role For Il-27 As a Therapeutic Target?mentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast to sgp130, the authors found no evidence for alternative splicing of the WSX-1 mRNA, but rather showed that metalloproteases were responsible for the generation of sWSX-1. They reported serum levels of about 10 ng/ml in healthy humans, and an increase in sWSX-1 levels in the serum of patients suffering from Morbus Crohn [97]. These data suggest that sWSX-1 acts a natural antagonist of IL-27 signaling in vivo, comparable to the role of sgp130 for IL-6 trans-signaling [18,94].…”
Section: A Role For Il-27 As a Therapeutic Target?mentioning
confidence: 77%
“…The different forms of sgp130 that can be found in the circulation at levels of about 400 ng/ml arise from alternative splicing of the gp130 mRNA [96]. Recently, a naturally occurring form of human sWSX-1 has been described, which is generated by CD4+ and CD8+ T cells, B cells, and myeloid cells [97]. In contrast to sgp130, the authors found no evidence for alternative splicing of the WSX-1 mRNA, but rather showed that metalloproteases were responsible for the generation of sWSX-1.…”
Section: A Role For Il-27 As a Therapeutic Target?mentioning
confidence: 98%
“…However, there are conflicting reports on whether the IL-27Rα chain is part of the receptor for IL-35: One report has indicated that IL-35R on T cells is composed of IL-12Rβ2 and gp130 or homodimers of these chains but that it does not require IL-27Rα (62); another has proposed that in B cells the IL-35R is composed of IL-12Rβ2 and IL-27Rα (63). The biology of IL-27R is further complicated by a recent report that T and B cells, as well as macrophages, release a soluble version of IL-27Rα that can block the ability of IL-27 to signal (64). This combinatorial biology remains a fascinating topic that has broad implications for thinking about the effects of IL-27 on the immune system, but one of the biggest challenges faced in this area is the lack of reliable reagents to study receptor expression and the lack of commercial sources of cytokines (IL-27p28, p28-CLF, IL-35) that have robust activity in multiple laboratories.…”
Section: The Il-27 Subunitsmentioning
confidence: 97%
“…59 Dietrich et al reported that varying levels of soluble IL-27Rα were produced by human CD4 + and CD8 + T cells, B cells, monocyte-derived dendritic cells, and monocytes. 59 While only speculation, it is interesting to question whether genetic deletion of IL-27Rα in only specific cells, such as the transferred T cells or recipient cells in the studies detailed above, could also eliminate or reduce this negative regulator of IL-27, resulting in dysregulated IL-27 signaling in remaining cells with functional IL-27Rα. The discovery of this endogenous, soluble antagonist for IL-27 is intriguing, and further research into its function and regulation could impact concepts of IL-27 biology and potential therapeutic manipulation.…”
Section: Il-27 and Inflammatory Bowel Disease: Clarity Amid The Confumentioning
confidence: 99%
“…13,78 Patients with active Crohn’s disease have also been shown to have both significantly increased serum IL-27 and soluble IL-27Rα relative to healthy controls; however, despite an overall positive correlation between these two values, the ratio of cytokine to soluble receptor varied widely among patients. 59 Table 2 highlights the evidence for IL-27 as a factor in human IBD.…”
Section: Il-27 and Inflammatory Bowel Disease: Clarity Amid The Confumentioning
confidence: 99%